Education on the use of Social Media as a Marketing Medium for Small Micro and Medium Enterprises (SME) in Cipamokolan Village during the COVID-19 Pandemic - Renda Sandi Saputra (International Journal of Research in Community Services, 2021)
The economy in Indonesia is now growing and developing, especially for SME (small micro and medium enterprises) businesses, in the micro, small and medium movement, many Indonesian people are opening small businesses, by marketing products that are still sought after by buyers, Many Indonesian traders have not used the internet or social media to market their products, even though there are many social media that can be used to market their products, such as Facebook, Instagram, Tiktiok and many more. Currently, social media or the internet can be accessed by anyone from all walks of life. including SME businessmen who use the internet as a means of providing and sharing information about products offered to consumers online. This study discusses how the use of social media by SME in marketing products during the COVID19 pandemic. The purpose of the research is to introduce traders in Cipamokolan village to be able to better utilize social media as a marketing tool in order to have a bigger market potential. This research method is a qualitative method using a descriptive approach by utilizing secondary data from various literatures such as books, journals/articles and homepages to access the latest data and information related to the impact of COVID-19 and the use of social media for the recovery of SME. The result of the research is that social media is an effective means of communication, can increase market share and help business decisions. The community in Cipamokolan village can increase sales volume by more than 100% if the information is updated every day and consistently.